SOCIALIZATION OF STANDARD INPATIENT CLASS (KRIS) TO EMPLOYEES OF ABDOEL WAHAB SJAHRANIE HOSPITAL (Jurnal Abdimas Administrasi Kesehatan, 2022)
The Health Social Security Organizing Agency (BPJS) is a legal entity to organize a social security program to ensure that all people can meet the basic needs of a decent life. For this reason, the government plans to remove the BPJS Kesehatan classification based on the class that is currently valid to a single class called a standard inpatient class (KRIS) or standard class. Community service will be held on October 1-5, 2021. The results of community service show that the existence of BPJS Kesehatan is very helpful in obtaining health services, but there are still many people who do not know about the policy of the BPJS Kesehatan standard class that will be applied. After the community service explained what is meant by standard classes, many respondents objected to standard classes and preferred grades 1, 2 and 3